Heart Failure Is Not Associated with a Poor Outcome after Mechanical Thrombectomy in Large Vessel Occlusion of Cerebral Arteries. (1st August 2019) - Schnieder, Marlena; von Glasenapp, Anneki; Hesse, Amelie; Psychogios, Marios N.; Bähr, Mathias; Hasenfuß, Gerd; Schroeter, Marco R.; Liman, Jan
Abstract : The impact of heart failure on outcome in stroke patients is not fully understood. There is evidence for an increased mortality and morbidity, but it remains uncertain whether thrombectomy in patients with large vessel occlusion (LVO) in the anterior circulation is less effective in patients with heart failure compared to patients without. Retrospectively, we analyzed echocardiographic data of all patients in our stroke database, who underwent mechanical thrombectomy (n=668) for the presence of heart failure. Furthermore, we collected baseline characteristics and neurological and neuroradiological parameters. In the analysis, 373 of the 668 patients of our stroke database underwent echocardiography. Of these 373 patients, 90 patients (24%) suffered from heart failure with reduced left ventricular ejection fraction measured by echocardiography according to the current guidelines. After adjustment for age, the Alberta stroke program early CT score (ASPECTS), and time from symptom onset to recanalization, the analysis revealed that thrombectomy in patients with heart failure and LVO is not associated with less favorable outcome measured by the modified Rankin Scale after 90 days (3 (0-6) vs. 3 (1-5); p=0.380). Moreover, we could not find a significant difference in mortality compared to patients without heart failure (11.0% vs. 7.4%; p=0.313).